Design and implementation of hardware‐in‐the‐loop simulation system for testing control and operation of DC microgrid with multiple distributed generation units. Issue 12 (6th February 2017) - Meng, Jianhui; Wang, Yi; Wang, Chen; Wang, Hui
Abstract : Direct current (DC) microgrid is characterised by attractive features such as high efficiency, reduced cost and needless for synchronisation. The control and operation of the DC mirogrid become significantly important with the high penetration of distributed energy resources. Therefore, development of an advanced platform for testing control and operation of the DC microgrid has attracted more and more attention nowadays. This study proposes a hardware‐in‐the‐loop (HIL) simulation system as a new method to develop and test control algorithms and operation strategies for the DC microgrid. The proposed HIL simulation system is composed of a RT‐LAB for real‐time simulation, an actual controller under test, a cRIO for coordination control and the DC microgrid management system for optimal operation. Both the actual controller of key research objects and coordination control with different time scales can be tested in the proposed HIL simulation system. Hence, the platform is designed for flexibility and universality. Moreover, configuration and communication of the HIL simulation system are illustrated in this study. Finally, simulation tests are carried out to show the validation of the proposed HIL simulation platform.